1997
DOI: 10.1146/annurev.physchem.48.1.745
|View full text |Cite
|
Sign up to set email alerts
|

New Epr Methods for Investigating Photoprocesses With Paramagnetic Intermediates

Abstract: Some of the significant advances in time-resolved multifrequency electron paramagnetic resonance (EPR) methods are reviewed, with the explicit focus on studies of light-driven processes and photoreactions in real time. Prominent examples are excited state electron transfer reactions with transient charge-separated radical pairs playing a central role. Paramagnetic intermediates and products are key functional states; thus EPR is the method of choice for their characterization. Photogenerated spin polarization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
108
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(110 citation statements)
references
References 242 publications
2
108
0
Order By: Relevance
“…The fourth advantage is a high absolute sensitivity which is of special significance for biochemical research where often only small amounts of the material are available. A more detailed discussion on the HFEPR research of the photosynthetic systems can be found in the recent reviews (Stehlik and Mobius, 1997;Mobius, 2000).…”
Section: High-frequency Epr Spectroscopy In Photosynthesis Researchmentioning
confidence: 99%
“…The fourth advantage is a high absolute sensitivity which is of special significance for biochemical research where often only small amounts of the material are available. A more detailed discussion on the HFEPR research of the photosynthetic systems can be found in the recent reviews (Stehlik and Mobius, 1997;Mobius, 2000).…”
Section: High-frequency Epr Spectroscopy In Photosynthesis Researchmentioning
confidence: 99%
“…This would be particularly interesting for the investigation of biradicals or light-induced radical pairs, such as those occurring in photosynthetic reaction centers (15). The nonlinear responses contain information about the correlation of the two electron spins.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, double site-directed spin labelling (DSDL) EPR techniques such as double electron-electron resonance (ELDOR) and its variants (Stehlik and Möbius, 1997) with the capability of the determination of intermediate and long-range distance restraints (10-70 Å) between specific sites in proteins, are the most extensively used EPR methodologies to obtain information on the extent and directionality of conformational changes in large biomolecular complexes including homooligomers (Focke et al, 2011;Rice et al, 2013).…”
Section: E Electron Paramagnetic Resonance Spectroscopymentioning
confidence: 99%